A Glycal Approach to the Synthesis of Pregnane Glycoside P571. Issue 11 (5th September 2018) - Liu, Chao; Ma, Yuyong; Pei, Chengfeng; Li, Wei; Yu, Biao
Abstract: Pregnane glycoside P57 is known as an active component of Hoodia gordonii, which has long been used as a diet with appetite suppressant property. Chemical synthesis of P57 demands installation of β‐cymarosyl linkage onto the steroid aglycone. The stereoselective formation of this special 2‐deoxy‐β‐glycosidic linkage has previously been proven to be difficult and thus a limiting step in the synthesis of P57 and its congeners. Herein, we report the glycosylation reactions with glycals as donors and TPHB (triphenylphosphine hydrobromide) as promoter and a convergent synthesis of P57 via a β‐selective glycosylation with a trisaccharide glycal donor. Abstract : Pregnane glycoside P57 with potent appetite suppressant activity was synthesized via a β‐selective TPHB‐promoted glycosylation with a trisaccharide glycal as donor.